2014
DOI: 10.15381/anales.v74i4.2704
|View full text |Cite
|
Sign up to set email alerts
|

Calidad del sueño en una facultad de medicina de Lambayeque

Abstract: Introducción: Una buena calidad de sueño es importante para que los estudiantes universitarios tengan un rendimiento académicosatisfactorio. No se cuenta con datos locales en relación a la frecuencia de mala calidad de sueño en universitarios de cienciasde la salud. Objetivos: Determinar la frecuencia de mala calidad de sueño en una facultad de medicina de la Universidad CatólicaSanto Toribio de Mogrovejo (USAT). Diseño: Estudio descriptivo transversal. Institución: Facultad de Medicina, Universidad CatólicaSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Sleep is an essential part of human health and life; this action has been related to different cognitive functions. It is well documented, that lack of sleep or poor sleep quality affects individual learning ability, academic performance and performance of neurocognitive functions (Gutiérrez-Ruíz et al, 2020;Jalali et al, 2020;Granados-Carrasco et al, 2013). This study aimed to determine the relationship between sleep quality and executive functions in first semester medical students at a public university in Jalisco.…”
Section: Discussionmentioning
confidence: 98%

CIERMMI Women in Science T-XVIII Health Sciences

MARROQUÍN-DE JESÚS,
MORALES-HERNÁNDEZ,
RAMÍREZ-BALTAZAR
et al. 2022
“…Sleep is an essential part of human health and life; this action has been related to different cognitive functions. It is well documented, that lack of sleep or poor sleep quality affects individual learning ability, academic performance and performance of neurocognitive functions (Gutiérrez-Ruíz et al, 2020;Jalali et al, 2020;Granados-Carrasco et al, 2013). This study aimed to determine the relationship between sleep quality and executive functions in first semester medical students at a public university in Jalisco.…”
Section: Discussionmentioning
confidence: 98%

CIERMMI Women in Science T-XVIII Health Sciences

MARROQUÍN-DE JESÚS,
MORALES-HERNÁNDEZ,
RAMÍREZ-BALTAZAR
et al. 2022
“…About 77.3% of the medical students evaluated reported poor sleep quality, and about half obtained a score for which they possibly required medical attention to treat this problem. A study in 2013 conducted at a medical school in Lambayeque-Peru among medical students from 1st to 6th years, which also used the Pittsburgh sleep quality questionnaire and used 5 points as a cut-off point for poor sleep quality, reported that they presented a prevalence of poor sleep quality in 79.9% of the students evaluated [ 22 ], another study in the same year and city, similar to the previous one, evaluated 247 health sciences students, and reported that the 85% of the respondents had a prevalence of poor sleep quality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, existen varias investigaciones que analizan la calidad de sueño en universitarios relacionada con algunos factores entre ellos la adicción al internet, por ejemplo, la realizada en la Universidad Católica Santo Toribio de Mogrovejo en Perú en la que el 85 % de estudiantes presentaron una calidad deficiente de sueño asociada a la carga académica que consecuentemente conlleva el uso de internet para realizar trabajos e investigaciones [13]. Del mismo modo, en un estudio llevado a cabo en estudiantes de múltiples universidades de China [14] se determinó que existe una asociación significativa entre el uso problemático de internet con la disminución de la calidad del sueño (r = 0,32, p < 0, 001).…”
Section: Desarrollounclassified